Demand for aflatoxin-safe maize in Kenya: Dynamic response to price and advertising - Hoffmann, Vivian; Moser, Christine; Herrman, Timothy (International Food Policy Research Institute, 2019)
This paper characterizes consumer demand for food safety and the dynamic impact of a social marketing campaign to promote a tested, third party verified maize flour in Kenya, where dietary exposure to the fungal toxin aflatoxin is a major public health concern. Consumption of high levels of aflatoxin can be fatal, but this is relatively rare. Of greater concern is chronic exposure, which has been linked in numerous studies to liver cancer and may also contribute to child stunting. A significant proportion of the maize consumed in Kenya, where it is the primary dietary staple, fails to meet regulatory standards. One study reported widely in the Kenyan press found that 65% of maize samples collected from 20 major millers did not meet the national standard (Gathura, 2011) and another based on over 900 samples collected from retailers found that 26% of branded maize flour was above this standard (Hoffmann and Moser, 2017).